A Phenetic Analysis of Korthalsia spp. in Sumatra Based on Morphological Characters - Fadjri Maarif; Himmah Rustiami; Priyanti Priyanti (Jurnal Penelitian Hutan dan Konservasi Alam, 2021)
Korthalsia (Blume) is a genus in the sub-family Calamoideae of the family Arecaceae. Research on a phenetic study of Korthalsia in Sumatra has never been published. The research was conducted to describe the specific characteristics of Korthalsia spp. in Sumatra and analyze their morphological character and similarity with a phenetic analysis. There were 85 herbarium specimens of Korthalsia deposited at the Herbarium Bogoriense (BO). Twenty-four vegetative and six generative characters were observed. Scoring was analyzed with a multinomial approach. The analysis was performed using the NTSys pc 2.02. The result showed that nine species of Korthalsia in Sumatra were distinguished based on their ocrea types, leaflets shape, and rachillae. The phenogram showed a similarity coefficient value of 0.53 for two main clusters, cluster A consisting of 4 species of Korthalsia (K. debilis, K. paucijuga, K. rigida, and K. rostrata) and Cluster B consisting of 5 species (K. echinometra, K. flagellaris, K. laciniosa, K. hispida, and K. robusta).